Building a regional HIV/AIDS database: challenges faced by West African specialist physicians and health librarians (2012)
The article investigates access and the use of the Internet among specialty doctors in five West African countries. It also looks at what information and communication technologies (ICT) are needed by health librarians to build a human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) database to carry out the West African regional project on HIV/AIDS information management. Two sets of questionnaires were designed: one for specialty doctors to assess their skills and the functionality of their institutional Internet access, the other to determine health librarians' ICT skills. The findings reveal factors such as power outages, irregular and slow Internet connection, nonexistent institutional Internet subscription, or half-day Internet access that resulted in minimal use of Internet by the specialty doctors. The health librarians, though skilled with information management, needed additional ICT training in Web design, electronic classification of resources, and most importantly, database building to function optimally on their project assignment. The findings led to recommendations such as improving Internet access in the West African tertiary institutions/hospitals and continuous ICT training for the health librarians.